Economic perspective of farmers indebtedness in suicidal prone area – Punjab, India - Jayappa, Vinay (Kansas State University, 2010)
The number of farmer suicides has been high in Andhra Pradesh, Karnataka, Kerala, Maharashtra, and Punjab since 2000. Farmers‟ suicide in India is reported to be due to the burden of debt. While it makes some sense to attribute farmer suicides in Kerala, Karnataka, Maharashtra, and Andhra Pradesh to indebtedness in view of the widespread poverty, it is more difficult to consider in the context of the Punjab which is known for its prosperity. Others have found that the prime cause for farmer suicides is indebtedness. The purpose of this research focuses on identifying and quantifying the reasons for farmers‟ indebtedness compared to non-indebted farmers in the same region. This was achieved by documenting the socio-economic profile of the farmers; studying the extent of indebtedness and pattern of capital use by farmers, and evaluating the farm business performance. Results obtained for the socio-economic profile of the farmer indicated that age, education, family size and landholding had a significant effect on the probability of a farmer being indebted. Family size had the largest effect on the probability of indebtness. A study on the extent of indebtedness and pattern of capital use showed that farmers depend on non-institutional loans for meeting their financial needs and some loans are used for non-agricultural purposes. Farm business performance of the sample respondents showed that they had a negative balance on farm business performance. Some of the methods to improve the situation would to improve and expand free and compulsory primary education, thereby reducing the debt incurred on education; diversifying towards high value/more remunerative crops, reviewing the system of subsidization of agricultural inputs, and expanding institutional sectors for providing loans at reasonable interest rates.
Keywords: Farmers debt; Farmer suicides; Punjab; India; Indebtedness; Economics, Agricultural (0503)